Pengaruh Intensitas Konsumsi Short-Form Video Terhadap Beban Kognitif Siswa Sekolah Menengah Atas - Muhammad Ihsan; Mastur Mastur; Hamsi Mansur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The paradigm shift in social media consumption toward short-form video formats has triggered maladaptive behavior that threatens high school students' working memory capacity due to continuous exposure to instant audiovisual information without adequate restoration intervals. This study aims to empirically examine the effect of short-form video consumption duration intensity on students' cognitive load based on the Cognitive Load Theory framework. A causal-associative quantitative approach using an explanatory survey method was implemented. Primary data collection was conducted online utilizing structured questionnaires via Google Forms administered to a single-shot sample of 167 student respondents determined through convenience sampling technique across two schools in Binuang District, Tapin Regency, namely MAN 2 Tapin and SMAN 1 Binuang. Data analysis techniques included descriptive statistical analysis and inferential testing using simple linear regression executed separately per dimension. The results demonstrate a significant asymmetrical pattern. In Model 1, daily usage duration has a significant positive effect on Intrinsic Load (p = 0,04 < 0,05) with a contribution of 5.0%. Conversely, Model 2 testing indicates that consumption duration has no significant effect on Germane Load (p = 0,090 > 0,05) with a contribution of only 1.7%. In conclusion, high duration of accessing short videos linearly increases brain workload in processing material density but fails to contribute to substantive academic schema construction. This research is expected to contribute to the development of educational technology studies regarding the phenomenon of cognitive load on students in the digital era.